Metacognition and self‐regulation on the road: A qualitative approach to driver attention and distraction. Issue 6 (6th November 2022) - Love, Steven; Truelove, Verity; Rowland, Bevan; Kannis‐Dymand, Lee
Abstract: This study aimed to explore the self‐regulatory experiences and perceptions of drivers' attentional processes on the road, via a metacognitive framework. A total of 46 Australian drivers participated in a phone interview and thematic analysis was applied to the data. The results revealed that effective self‐reported attention regulation was perceptually contingent on: driving experience, metacognitive skills used to regulate attention, and strategies to sustain attention. The perceptual difficulty of driving environments was shown to impact on self‐reported arousal, and thus the perceived ability to control and sustain attention. Similarly, cognitive confidence, and metacognitive beliefs about worry and mindless driving were shown to not only influence the tendency to engage in worry and mindless driving, but also the subjective ability to self‐regulate attention whilst doing so. This study has provided evidence for the potential of metacognitive concepts to help better understand the process of attentional lapses and difficulties on the road.